Three Simple Software Extensions for Automatic Presentation of Radiation Induced Toxicity, Sequelae and Treatment Outcomes, for Increasing Safety in Daily Therapeutic Routine, and for Enhancing Patient Comfort - Robert Michael Hermann; Michael Schober; Ulrich Martin Carl; Mirko Nitsche (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2016)
Background: Simple software extensions to already existing software-infrastructure can monitor treatment results, increase patient safety and enhance patient comfort in a very cost-effective way. This is of particular interest due to the increasing implementation of quality management in radiotherapeutic treatment sites as well as due to the external cooperation in cancer centers. In this article, we present three different tools. Results: First, "ToxReview" is a program extension to "MOSAIQ" 02.10. It correlates automatically radiation induced toxicity and treatment outcomes with therapeutic concepts (target volumes, radiation doses etc.). Data are shown in a simple tabular form.Second, "Patient  Recognition"  is  a  JAVA  based  program  extension  that  aims  to  minimize  the risk of mix-ups between patients. It does not need a MOSAIQ license. It identifies the actual patient uploaded in the treatment control station. On a monitor next to the treatment room entrance a portrait and the name of this patient is shown, enabling the assistance staff and the patient himself to check that his specific data are uploaded.Third,  the  add-on  "Jukebox"  enables  to  play  patient  individualized  music  and  entertainment programs in the radiation room during treatment. No additional efforts are necessary for the assistance staff. Conclusion: We present customer programmable software extensions with high value in daily clinical practice, to expand the possibilities of the pre-existing IT infrastructure.Quality management,patient safety and patient satisfaction are substantially increased.